KOH activation of carbon electrodes for enhanced capacitive dechlorination: Performance and mechanisms - Jianna Jia; Chang Lu; Jinlong Han; Wenrui Wang; Kailei Zhang; Zhijun Ren (PLoS ONE, 2026)
Coal transportation terminals produce wastewater containing high concentrations of chloride, which can cause corrosion of equipment and be hazardous to the environment. Capacitive deionisation (CDI) has been discussed as an alternative to conventional dechlorination methods, given that it consumes low energy and avoids secondary pollution. This paper involved the development of a KOH-modified activated carbon (KOH-AC) electrode, which must be used to improve the chloride removal performance of CDI. The obtained characterization results showed that, under the activation of KOH, the specific surface area of activated carbon (104.48 m 2 /g to 1390.88 m 2 /g) was greatly intensified, the pore structure became more uniform, and plentiful oxygen-containing functional groups were formed, improving electrochemical activity and ion adsorption capacity. In optimal operating conditions (1.2 V, 20 mL/min), the KOH-AC electrode obtained a chloride ion removal efficiency of more than 80% and was extremely stable even after numerous adsorption-desorption cycles. Moreover, the CatBoost exhibited high accuracy in predicting chloride removal efficiency (R 2 = 0.9114). The shap analysis revealed that the flow rate and influent NaCl concentration were the most significant factors for dechlorination. This study provides insights for the efficient removal of chlorinated wastewater in coal transportation terminals, while the constructed model offers a reference for precise treatment.